2017
DOI: 10.1016/j.oraloncology.2017.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and genomic characterization of primary salivary duct carcinoma cell line

Abstract: Objectives To develop and characterize in vitro salivary duct carcinoma as a surrogate for functional studies. Materials and Methods Cells were dispersed from tumor tissue fragments under sterile conditions in RPMI media. Disassociated cells were cultivated, immortalized with hTERT and propagated for more than 100 passages. Morphologic, linage, cytogenetic and genomic analyses were performed on different passages of cell line and primary tumor. Soft agar growth was performed. Results Analysis of cytomorpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…To date, there are several previous reports on the establishment of cell lines for SGC [27][28][29][30][31][32][33][34][35] . In terms of SDC cell line, MDA-SDC-04 is the only SDC cell line established using a 2-dimensional culture reported until now 31 , while Li et al reported that the line requires an immortalization process and loses chromosomal aberrations by long-term passaging without any tumor-forming potential in xenografts. Thus, it is di cult to establish SGC cell lines using traditional 2-dimensional culture that reproduces the original tumor characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are several previous reports on the establishment of cell lines for SGC [27][28][29][30][31][32][33][34][35] . In terms of SDC cell line, MDA-SDC-04 is the only SDC cell line established using a 2-dimensional culture reported until now 31 , while Li et al reported that the line requires an immortalization process and loses chromosomal aberrations by long-term passaging without any tumor-forming potential in xenografts. Thus, it is di cult to establish SGC cell lines using traditional 2-dimensional culture that reproduces the original tumor characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…SDC cell lines female derived RET981 (7,41), male derived MDA-SDC-04 (SDC-04; ref. 42), and MAC (43) were used. Both RET981 and SDC-04 cells express full length AR.…”
Section: Sdc and Prostate Cancer Cell Linesmentioning
confidence: 99%
“…For an epithelial cell line, such observations are based on examination of the cellular morphology and expression pattern of the epithelial marker cytokeratin [ 9 ]. In addition, any changes in chromosomes that may have been induced by the immortalization protocol are screened by karyotype analysis [ 10 ] and/or the presence of gene mutations from the progenitor cell using whole-exome sequencing [ 11 ]. Actually, ovarian cancer has been known to originate from the ovarian surface epithelium (OSE) since the mid-90s to early 2000s [ 12 – 15 ].…”
Section: Introductionmentioning
confidence: 99%